Contraceptive practices and contraceptive counselling in high-performance Portuguese athletes - Gomes, I. M. N.; Coelho, A. R.; Metello, J. L. B. L. (Scientific Journal of Sport and Performance, 2022)
We present an observational, prospective, descriptive study of answers collected through an online self-assessment questionnaire in High Performance Portuguese Athletes aged 18 years old or over. The main objective was to evaluate contraceptive practices, menstrual patterns and contraceptive counselling in these athletes. Overall, 115 women aged between 18 and 39 years were studied, from 18 different sports. In our sample, most athletes used some type of contraception. Most believed that they had a better performance after menstruation and that starting contraception did not interfere with their performance. However, a high number of athletes believes that contraceptives are contraindicated for sports.